(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
Suzanna Arundhati Roy is an Indian author and politicalactivist who is best known for the 1998 man booker prize for fiction winningnovel The God of Small Things(1997) and for her involvement in environment and human rights causes. Roy’snovel becomes the biggest selling book by a non-expatriate Indian author.Arundhati Roy was born in Shillong early in her career; Roy worked fortelevision and movies. Roy began writing her first novel, The God of Small Things in 1992, completing it in 1996. The book issemi-auto biographical and a major part captures her childhood experiences inAymanam. The publication of The God ofSmall Things catapulted Roy to instant international fame. It was listed asone of the New York Times notables’ books of the year for 1997. From thebeginning, the book was also a commercial success. Roy received half a millionpounds as an advance. Since The God ofSmall Things Roy has devoted herself mainly to non-fiction and politics,publishing two more collections of essays as well as working for social causes.She is a spokesperson of the anti-globalization movement and a vehement criticof neo-imperialism and the global policies Of the United States. She alsocriticizes India’s nuclear weapons policies.